Graph Theory in Paris Proceedings of a Conference in Memory of Claude Berge - Bondy, Adrian; Fonlupt, Jean; Fouquet, Jean-Luc; Fournier, Jean-Claude; Ramírez Alfonsín, Jorge L. (Trends in Mathematics, 2007)
In July 2004, a conference on graph theory was held in Paris in memory of Claude Berge, one of the pioneers of the field. The event brought together many prominent specialists on topics, such as perfect graphs and matching theory, upon which Claude Berge's work has had a major impact. This volume includes contributions to these and other topics from many of the participants.